2020
DOI: 10.3390/rs12213578
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-Temporal Evaluation of Water Storage Trends from Hydrological Models over Australia Using GRACE Mascon Solutions

Abstract: The Gravity Recovery and Climate Experiment (GRACE) data have been extensively used to evaluate the total terrestrial water storage anomalies (TWSA) from hydrological models. However, which individual water storage components (i.e., soil moisture storage anomalies (SMSA) or groundwater water storage anomalies (GWSA)) cause the discrepancies in TWSA between GRACE and hydrological models have not been thoroughly investigated or quantified. In this study, we applied GRACE mass concentration block (mascon) solutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 62 publications
(113 reference statements)
0
7
0
Order By: Relevance
“…The TWSA of the YRB for the period May 2002-June 2020 can be calculated based on GRACE and GRACE-FO RL06 Mascon data [60] (Figure 2). Monitoring results from GRACE and GRACE-FO showed that the TWSA presented characteristics of significant interannual variation.…”
Section: Twsa Precipitation and Runoff Characteristics In The Yrbmentioning
confidence: 99%
“…The TWSA of the YRB for the period May 2002-June 2020 can be calculated based on GRACE and GRACE-FO RL06 Mascon data [60] (Figure 2). Monitoring results from GRACE and GRACE-FO showed that the TWSA presented characteristics of significant interannual variation.…”
Section: Twsa Precipitation and Runoff Characteristics In The Yrbmentioning
confidence: 99%
“…Compared with Spherical Harmonic (SH) solutions, mascon solutions can be applied from the regional to global scales. In addition, mascon solutions do not require de-striping and signal restoration, which also have a higher signal-to-noise ratio [30].…”
Section: Grace Datasetsmentioning
confidence: 99%
“…These measurements capture changes in mass primarily attributed to water movement in the Earth's water cycle (Tapley et al., 2004). Hence, the GRACE/GRACE‐FO observations have been extensively utilized in hydrologic research (Scanlon et al., 2016), primarily including the evaluation of large‐scale terrestrial water storage (TWS) changes, especially those related to extreme droughts (Boergens et al., 2020; Chen et al., 2009; Leblanc et al., 2009; Long et al., 2013; Thomas et al., 2014) and floods (Chen et al., 2010; Reager et al., 2014), estimation of the groundwater extraction (Feng et al., 2013; Rodell et al., 2009; Scanlon et al., 2012), and promotion of further hydrological model development (Scanlon et al., 2018, 2019; Yang et al., 2020). These applications have significantly enhanced our understanding of the influences of climate changes and anthropogenic activities on TWS anomalies (TWSA) (Rodell et al., 2018; Tapley et al., 2019).…”
Section: Introductionmentioning
confidence: 99%